TOP-DOWN AND BOTTOM-UP PROCESSING IN LISTENING. WHICH ONE IS PROBLEMATIC?: A CASE OF UNIVERSITAS PGRI SEMARANG - Sukma Nur Ardini (ETERNAL (English Teaching Journal), 2015)
To enhance students’ ability in listening skill, the lecturer needs to understand what problems faced by their students. Since listening is still a big issue for English learners in Indonesia, so the processing of Top Down and Bottom Up need to be figured out. Top-Down processing refers to the use of schemata or knowledge of learners to understand the information received, while the Bottom-Up processing refers to the process of understanding the information through the analysis of sound, sense of the word, and grammar. This study wanted to investigate what problems do students have in learning listening since the observation result showed that students’ listening grade is low. A case study research design was applied in this study. Thirty students of first semester of Universitas PGRI Semarang in the academic year 2015/2016 became the sample of this study. The data were collected through observation, questionnaire, and interview. The result showed that 90% of the students found that Bottom Up processing is more problematic than Top Down processing (10%). The interview result showed that 44% students have difficulty in vocabulary and 56% in pronunciation. Those problems make them difficult to catch what the speaker says. It leads to another problems that is Top Down processing which needs Bottom Up as the basic competence. Therefore, it suggests to lecturer that Bottom Up, which involved vocabulary and pronunciation, is matters for students to achieve the listening competence well.